The Role of Vitamin D in Different Stages of Nephropathy in Type 2 Diabetic Patients and its Correlation with Transforming Growth Factor Beta-1 (TGF-\(β\)1): A cross Sectional Study - Liji Kavuparambil; Ashok Kumar Pammi (Recent Updates in Disease and Health Research Vol. 7, 2024)
Aim: The present study analyses the role of vitamin D status in different stages of type 2 diabetic nephropathy and its correlation with transforming growth factor beta-1. Background: A microvascular consequence of diabetes mellitus (DM), diabetic nephropathy (DN) is becoming more common each year. Patients with diabetic nephropathy should have their vitamin D levels regularly monitored, as low vitamin D levels may be associated with an increased risk of developing diabetic nephropathy. Studies evaluating the role of vitamin D in DN are few. Conflicting data is available on the correlation between vitamin D and Diabetic Nephropathy. Studies revealed the sample population is Vitamin D deficient. Therefore, it is important to understand the correlation of Vitamin D with severity of Diabetic nephropathy and its role in fibrogenesis. Methods: A 1.5-year cross-sectional study of 120 diabetic patients, 60 with nephropathy and 60 without nephropathy patients enrolled to MES Medical College. Patients with heart, liver, or thyroid disease, as well as those on dialysis, were excluded from the study. The VITROS 5600 integrated system were used to measure fasting blood sugar (FBS), HbA1c, creatinine and vitamin D. Transforming Growth Factor Beta-1 (TGF-\(β\)1) is measured using ELISA technique. According to HbA1c and estimated glomerular filtration rate (eGFR) values, the study population is divided into two groups. The statistical package for the social sciences (SPSS) software was used to conduct the analysis. The level of significance was calculated at 95%. Results: Compared to diabetic individuals without nephropathy, those with nephropathy had much-decreased vitamin D levels. Serum creatinine, urea, HbA1c, and TGF-\(β\)1 in individuals with diabetic nephropathy revealed a highly significant negative association with vitamin D status, whereas eGFR showed a highly significant positive correlation. Experimental studies, observational studies, and clinical trials have indicated the possible effects of vitamin D in protecting against the progression of DKD and preserving the integrity of the glomerular filtration barrier. These studies have highlighted the necessity of clinicians to be alert to vitamin D deficiency in patients with DKD and the importance of supplementation among high-risk groups. Conclusion: A deficiency of vitamin D has a role in the development and severity of DN, and showed a highly significant correlation with the regulator of fibrosis, TGF-\(β\)1. This finding indicates that vitamin D could be an important factor for the development and progression of Diabetic nephropathy. So supplementation of vitamin D may slow down the progression of DN.